Desain Modul Data Konsumen dan Pemasok untuk Sistem Informasi E-Commerce Ultra Mikro Usaha Mikro Kecil dan Menengah Berbasis Website - Tasya Aprilla Almuqaramah Yuton; Irwan Adi Pribadi; Yohana Tri Utami (Jurnal Pepadun, 2023)
Given the rapid development of technology, it makes competition in the business world and requires UMKMs (Micro, Small and Medium Enterprises) to keep up with the times, so that they can achieve the desired targets in marketing and so that information is more quickly received by consumers. Â During this pandemic, many people lost their jobs and switched to running their own businesses to meet their daily needs so it is possible for people to open Ultra Micro UMKM Businesses with a capital of between 2 to 5 million rupiah. With the number of UMKMs developing in Bandar Lampung City, competition is created in the business world, a strategy for sales is needed that can make it easier for sellers and consumers to buy products. Web-based information systems are one way to compete creatively in the business world. This E-commerce Information System has a database of product sales, product suppliers, product data, and sales reports. The database of product data is products purchased through suppliers, then the product sales database is generated from products that have been sold through online sales carried out locally within the scope of Bandar Lampung City. This research method uses Black-box Testing and has involved 3 examiners and showed a good response to the suitability of UMKM E-Commerce needs.